Major problems in Asian American history documents and essays - Kurashige, Lon 1964-; Murray, Alice Yang (Major problems in American history series., 2003)
"Designed to encourage critical thinking about history, the [book] introduces students to both primary sources and analytical essays on important topics in U.S. history. [The book] presents ... selected group of readings in a format that asks students to evaluate primary sources, test the interpretations of distinguished historians and others, and draw their own conclusions"--P. [4] of cover.